1990
DOI: 10.1007/bf00041381
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal nitrogen and carbon concentrations in white, brown and woody fine roots of sugar maple (Acer saccharum Marsh)

Abstract: Small diameter ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…amino acids, organic acids and sugars), and their rate of turnover inside root tissues was greatest in the most actively growing root regions (Jones and Darrah 1996). The higher major nutrient concentrations (N, P, K) in young white roots in comparison to pigmented roots reported here are also consistent with earlier studies showing nutrient translocation from older roots towards more physiologically active parts of the plant (Goldfarb et al 1990;Volder et al 2005). Our study also indicated that older pigmented roots had much greater structural, cell wallassociated C in comparison to younger roots.…”
Section: Discussionsupporting
confidence: 92%
“…amino acids, organic acids and sugars), and their rate of turnover inside root tissues was greatest in the most actively growing root regions (Jones and Darrah 1996). The higher major nutrient concentrations (N, P, K) in young white roots in comparison to pigmented roots reported here are also consistent with earlier studies showing nutrient translocation from older roots towards more physiologically active parts of the plant (Goldfarb et al 1990;Volder et al 2005). Our study also indicated that older pigmented roots had much greater structural, cell wallassociated C in comparison to younger roots.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Lipp and Andersen (2003) found that white roots of Pinus ponderosa trees comprise a relatively small portion of total root biomass in the field. Classification by root color was frequently used in previous studies, often as proxy for root age, white being regarded as the color of young root segments (Goldfarb et al, 1990;Hendrick and Pregitzer, 1992;Hassan et al, 2008). In this study, however, brown root tips seemed as vital as white ones, and the relatively short duration of the experiment deems it unrealistic that many white root segments already matured to brown terminal roots.…”
Section: 05)mentioning
confidence: 74%
“…Root order class 1 + 2 represents the two terminal root orders (i.e. root tips and the next root segment; additional details on color and root order classification are in Goldfarb et al, 1990, andRewald et al, 2011, respectively) and could be distinguished by color with certainty; we name our classification scheme "extended centripetal root order classification." No spatial segregation between the two different terminal root order classes was noticed.…”
Section: Plant Allometry and Root System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, nutrient concentration within fine roots varies inversely with root diameter (Goldfarb et aI., 1990;Vogt et aI., 1991). Increase in concentrations of phosphorus, nitrogen, carbon, magnesium, sulphur and sodium with decreasing root diameter is known for Pinus sylvestris (Berg, 1984) and Acer saccharum (Goldfarb et al, 1990). This explains the better capabilities of fine roots as litter than coarse roots.…”
Section: Biochemistry Of Root Litter Degradationmentioning
confidence: 96%